A Quality Analysis of the Last Decade's Most Heavily Cited Data Relative to Outcomes After Penile Prosthesis Placement - Chouhan, Jyoti D.; Pearlman, Amy M.; Kovell, Robert C.; Terlecki, Ryan P. (Journal of sexual medicine, 2020)
The penile prosthesis has been used for men with erectile dysfunction for nearly 5 decades. Although many articles examine various outcome measures, wide variability exists in the quality of these studies. We sought to critically evaluate the most referenced literature related to penile prosthesis outcomes over the last 10 years. A PubMed search of the indexed English literature was performed using the search terms “prospective,” “penile prosthesis,” and “outcomes”, and all relevant publications from 2009 to 2019 were reviewed. In addition, we performed a Google Scholar search for the same interval using the search term “penile prosthesis outcomes” to evaluate manuscripts which have been most commonly cited. The most heavily cited manuscripts were sorted for relevancy using Google's internal algorithm, and then, the articles were reviewed by the authorship team for appropriateness of the subject matter. Articles with less than 10 citations were excluded. We used the Oxford Center for Evidence-Based Medicine Criteria as part of our evaluation of the published data involving independent research, as opposed to review articles summarizing previously published findings. We evaluated the most-cited literature of the past decade relevant to penile prosthesis outcomes and reported the major findings in regards to infection, erosion, extrusion, device reliability, and satisfaction (both the patient and partner). The majority of these studies are retrospective in nature. From our review of the most commonly cited studies, there was no high-level evidence published in this area within the last 10 years. There are multiple barriers to producing these types of studies in the evaluation of penile prosthesis outcomes. Using the most commonly cited articles allows us to understand the data that are being cited in other new publications. Focusing on the most cited articles on penile prosthesis outcomes in the last 10 years is a limitation as there have been many more studies published in this area. While many studies have examined penile prosthesis outcomes, most of the heavily cited literature consists of low-level evidence. Higher quality research is necessary to better assess penile prosthesis outcomes. Chouhan JD, Pearlman AM, Kovell RC, et al. A Quality Analysis of the Last Decade's Most Heavily Cited Data Relative to Outcomes After Penile Prosthesis Placement. J Sex Med 2020;17:861–869.